Language Processing Abilities in a Multilingual Context: The Role of Linguistic Background among Students in Amman, Jordan - Лукман Рабабах (Психолінгвістика, 2024)
Aim. This quantitative experimental study aims to examine the impact of linguistic background on language processing abilities among learners at a language academy in Amman, Jordan. The purpose of the study is to investigate how different linguistic backgrounds influence language processing skills specifically in the areas of grammar, syntax, and semantics.